1996
DOI: 10.1021/jp9520355
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Rate Coefficients for the Reactions of OH Radicals with Some Monoethylene Glycol Monoalkyl Ethers

Abstract: Rate coefficients for the reactions of OH radicals with monoethylene glycol monoalkyl ethers have been determined by the competitive method at 297 ± 3 K. Relative to the value k OH+hexanol = 12.5 × 10-12 cm3 molecule-1 s-1, the rate coefficients are as follows (in units of 10-12 cm3 molecule-1 s-1):  methoxyethanol, 10.8 ± 1.1; ethoxyethanol, 14.5 ± 0.4; propoxyethanol, 16.4 ± 0.7; butoxyethanol, 19.4 ± 2.0. In a second set of experiments relative rate coefficients were measured for the same series of glycol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 9 publications
8
32
3
Order By: Relevance
“…PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4]. A 43% ethyl formate yield was reported for 2-ethoxyethanol; a 35% butyl formate yield was reported for 2-butoxyethanol; while a 47% propyl formate yield was measured for 2-propoxyethanol [1,4].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…PF observation is consistent with previous studies of the hydroxyl reaction products of 2-ethoxyethyl acetate and ethyl 3-ethoxypropionate: the methylenes next to the ether oxygen are activated [4,5,10,11,21]. The PF product yield is larger than the trend expected using the data for 2-ethoxyethanol and 2-butoxyethanol that was reported by Stemmler et al [1,4]. A 43% ethyl formate yield was reported for 2-ethoxyethanol; a 35% butyl formate yield was reported for 2-butoxyethanol; while a 47% propyl formate yield was measured for 2-propoxyethanol [1,4].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the similarity between the calculated versus the measured k 2PEOH supports these "reactive site" assignments. The k 2PEOH value reported in Stemmler et al [1] is somewhat smaller than the calculated value and the value reported here, but that discrepancy may be due to the OH rate constant of the reference used. The OH rate constant of 1-hexanol, the reference compound used in Stemmler et al, has been recently remeasured by Aschmann et al [25].…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations